CREATIVE ECONOMIC EMPOWERMENT OF “RED GINGER” IN ADDICT PRISONERS - Setiawan, Helmi Budi; Equatora, Muhammad Ali (Journal of Management Small and Medium Enterprises (SMEs), 2025)
Drug abuse is a phenomenon that often occurs in Indonesia, one of which is the case of drug abuse crimes which makes many people have to deal with the laws in Indonesia. In this research, the research design used is a case study. The results of the study are Empowerment for prisoners, especially addict prisoners, which is carried out at the Gunung Sindur class IIA Narcotics Prison in addition to improving the skills of prisoners can also provide a form of productive activity for addict prisoners so that they can slowly escape drug dependence with obstacles in its implementation, such as the condition of the production room, the ability of prisoners to participate in empowerment, technology that is still manual and there is still a sense of addiction to prisoners. The proposed coaching program is based on the obstacles of the previous program, so the researchers propose a program called the Community-Based Drug Rehabilitation Program through collaboration with the Bogor Regency Social Service at the Gunung Sindur Class IIA Narcotics Prison. Keywords: Prisoners; Narcotics; Empowerment; Development